Anti‐coagulant therapy with dabigatran for cystic fibrosis patients. Issue 8 (29th April 2016) - Bansal, Manvi; Ren, Clement L.
Summary: Patients with cystic fibrosis (CF) are at increased risk of venous thromboembolism, especially in association with central venous catheter use. Coumarin drugs and low molecular weight heparin are frequently used for anti‐coagulant therapy, but are more challenging to administer in CF patients. Dabigatran, an oral thrombin antagonist, is an alternative anti‐coagulant medication, but its use in CF has not been reported. We describe our experience in successfully using dabigatran for long‐term anti‐coagulation therapy in two CF patients. Our experience suggests that dabigatran can serve as an option for anticoagulation therapy in CF.Pediatr Pulmonol. 2016;51:E29–E30 . © 2016 Wiley Periodicals, Inc.